Expert System for Diagnosing Types of Diseases in Human Intestine Organs Using the Certainty Factor Method - Elis Nurhayatmi; Zaenal Muttaqin; Ahmad Sugiyarta; Ryan Naufal Hay’s (Universitas Serang Raya, 2019)
Intestine is one of the organs of the digestive system in the human body which is shaped like pipes and act as gatekeeper food system for our bodies. Many people do not noticed his intestines health because they are too busy with his activity, or lazy to go to the doctor, even when hospital were many visitors there is also felt a lot of to waste time to queue up because they want to get their turn to be checked and a lot of costs to be incurred. This research discusses about creating expert system to diagnose intestinal diseases using certainty factor method. Applications developed with Visual Basic programming language with MySQL as its database. The results of this research able to do early diagnosis of the symptoms that is felt system users, and provide diagnostic results such as type of disease suffered, prevention and its information.